PELATIHAN KETERAMPILAN MC DAN DIRIGEN IBU-IBU PKK DESA KINCANG KECAMATAN JIWAN KABUPATEN MADIUN - Maria Magdalena Widiantari; Fikri Hasan (Universitas Merdeka Madiun, 2021)
Public communication skills are an unavoidable demand in an organization. Being an MC or being a speaker is a skill that must be possessed, and for that it needs to be learned. The MC and Dirigen Training for PKK’s member of Kincang will be divided into several sections, namely general communication skills, public speaking, overcoming nervousness, and practice being MC and conductor. The purpose of this training is that PKK’s members have good skills in public speaking so that they can carry out PKK's internal events well and smoothly. In addition to being useful in terms of hosting events as MCs, this public speaking skill is also useful so that PKK members are accustomed to speaking in public, including delivering socialization materials in other task. By having good communication skills, PKK’s member can play a role in bringing official events in the village government so that they no longer need to hire or pay for a professional MC.